Real area of contact and tractions on the patterned surfaces generated by spinodal decomposition and amplified instability - Lee, Wonhyeok; Eriten, Melih (Frontiers in Mechanical Engineering, 2023)
Past decades featured significant advancements in additive and micromanufacturing that facilitated the creation of functional patterned surfaces with impressive spatial resolutions.However, these techniques are expensive and require a considerable amount of time and energy, and hence lack scalability to practical surfaces. Recent techniques employing spinodal decomposition and instabilities amplified via centrifugal acceleration offer viable and cheaper alternatives. The patterns created by those techniques, however, vary randomly in geometry.When interfacing those patterned surfaces with other components and under self-contact scenarios, geometric variations lead to stress concentration and abrupt failure around the contact. In this study, we investigate numerically real contact areas, contact tractions, and stress concentration. We generate patterned surfaces in congruence with actual surfaces created by those techniques. Then, we conduct normal-contact analyses of those surfaces boundary element method (BEM) under nominal mean pressures ranging from 0.001E* to E* , where E* is the contact modulus. We record real contact areas and stress concentration as a function of nominal mean pressures. We compare these values with the analytical solutions from sinusoidallypatterned and randomly rough surfaces. Randomness in pattern geometry is primarily influenced by the processing parameters such as the degree of anisotropy in spinodal decomposition and acceleration in amplified instabilities. To understand the influence of the processing parameters, we perform a parametric study. We find isotropic spinodal decomposition creates patterns that deliver contact area and traction distributions similar to randomly rough surfaces, and lead to highstress concentrations. Such high-stress concentrations are expected to occur under self-contact loading scenarios, and thus can explain the compromised resilience and strength in recentlyproposed spinodal metamaterials. For patterned surfaces created by amplified instabilities, high-stress concentrations are obtained for the surfaces created at high accelerations. At high accelerations, increased elastic instabilities and stochastic growth result in a more skewed and broader distribution in heights. Therefore, high-stress concentrations are inevitable. To account for combined loading scenarios, we conduct additional simulations on the same surface patterns with frictional pre-sliding contacts. We find the frictional tractions play a secondary role in stress concentrations where the primary factor is the processing parameters determining the degree of randomness in pattern geometry.